PERIHAL ANAK ANGKAT DAN KEWARISANNYA DALAM PERUNDANG UNDANGAN - fitria agustin (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2024)
Abstract Adopted children are defined by some societies in which adopted children are sometimes viewed as common in a family. The factor of adoption as having a family relationship, as well as complete absence of status with the child, is considered one of the most substantial reasons for basing adoption. Of course in law, the adoption of a child would stipulate a new law in the family position, one of which was concerning his sanity. This paper USES a type of normative sociative juxtative study where research refers to law as a living and developing norm in societies the data type is library research, where data is reviewed from library studies, analyzing a wide range of sources/literature. The data analysis is presented by analytic analytic methods, which are presented in the form of descriptions, statements, and not Numbers. The result states that the position of adopted children/parents to the law of heirs who are both inheritors, according to the compilation of islamic law adopted children/adoptive children have the right to receive a 1/3 compulsory will if adopted children do not receive the inheritance. If in addition to Islam, ramming can be governed by the laws of its indigenous two, or if it chooses to submit to civil law. Keywords: heir, adopted son, law, Islam